Penyuluhan Hukum: “Penegakan Hukum Terhadap Kasus Perempuan Dan Anak Berhadapan Dengan Hukum Di Pesantren Hidayatulah, Kelurahan Batakte, Kecamatan Kupang Barat, Kabupaten Kupang - A Resopijani; Ishak A Tungga; Daud Yaferson Dollu (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The findings in a 2021 study entitled "Law Enforcement of Cases of Women and Children Confronting the Law During the Covid-19 Pandemic at the Selandahan Police in Timor, that there is still a lack of public understanding of regulations relating to children, it is necessary to socialize regulations - these regulations, so that the initial stage of implementing the activity will be carried out at the Hidayatulah Islamic Boarding School, Batakte Village, West Kupang District, Kupang Regency. Juvenile Crime and law no. 11 of 2012 concerning the Juvenile Criminal Justice System in Indonesia is entering a new era in its development, one of the reforms in criminal law in Indonesia is the regulation of criminal law.Protection against Children also include interests related to child welfare, protection of children in conflict with the law (ABH), is a shared responsibility, namely all components consisting of the community, law enforcement officials as an extension of the government in efforts to protect not only children as perpetrators, but also children as victims and witnesses. One of the backgrounds of the service team at the Hidayatulah Islamic Boarding School, Batakte Village, West Kupang District, Kupang Regency is that universities are obliged to organize education and teaching, research, and community service. According to the law on higher education, community service is an activity of the academic community that utilizes science and technology to advance social welfare and educate the nation's life. This activity aims to provide legal understanding to the community and implement the Tri Dharma of Higher Education. This service uses counseling methods, and free sharing of legal knowledge which is carried out by presenting materials relating to the juvenile criminal justice process, to community members at the Hidayatulah Islamic Boarding School, Batakte Village, West Kupang District, Kupang Regency by a team of devotees from Faculty of Law, University of Nusa Cendana, Kupang. Based on the results of the service implementation, it can be concluded that; 1). There is limited knowledge and understanding of the community, in this case the students of the Hidayatulan Islamic Boarding School, if there are cases related to the process that must be carried out by the parties, especially the victims. 2) Limited knowledge and understanding of the community, in this case Hidayatulah Islamic Boarding School students regarding what to do when children face the law, 3) There are still many children's rights that are still neglected and still have to provide protection and a process of handling through legal channels for the benefit of the future in front of the child. 4) Lack of public knowledge, in this case Hidayatullah Islamic Boarding School students, about regulations relating to children, specifically the law on the juvenile criminal justice system. 5). The presence of the service team can make a positive contribution in terms of providing free legal understanding for the community at the Hidayatulah Islamic Boarding School, Batakte Village, West Kupang District, Kupang Regency, through legal counseling activities.